Capacidades de pensamento crítico em atividades experimentais investigativas : uma perspectiva para a abordagem metodológica da pesquisa de desenvolvimento - Silva, Luiz Henrique Barros da (2020)
It is known that it is increasingly necessary to stimulate students' critical and reflective thinking in order to contribute to their ability to make conscious decisions and acquire positions based on solid ideas. This need extends not only in school contexts, but also in contexts outside school life. Tenreiro-Vieira and Vieira describe critical thinking as the ability to structure their choices voluntarily and based on arguments. Some authors argue that investigative activities emerge as an approach that allows the development of students' autonomy, since they ask them to make decisions about problems. Considering this context, this research aims to investigate what elements an Investigative Activity needs to present in order to potentially mobilize Critical Thinking capacities. As a methodological route for the development of investigative activities for the promotion of critical thinking, design research, also known as development research, was adopted. Educational design research can be understood as the set of research approaches that seek to generate knowledge about the problems of educational practice, increasing knowledge about them. Thus, this research adopts a system of elaboration - validation - re-elaboration, in which the successive validations are understood as part of the process of generating knowledge about the material that one seeks to develop to reach a certain objective. The results of the validations were analyzed using Content Analysis. Among some of the results achieved, it was observed that presenting the investigation problem of an Investigative Case can be an important mechanism to consolidate the investigative character of the activity, it can be observed that from the procedures adopted in the research it was possible to observe evidence that mobilizes the ability to "investigate" critical thinking. It was also observed that, although the activities were designed to express a capacity for critical thinking, the activities express capacities in different areas.